Sistema de monitoramento e gerenciamento de energia baseado no Protocolo MQTT para unidades com geração distribuída - Costa, Kevin Rabelo (2021)
In Brazil, the distributed generation was implanted in 2012 through the RN nº 482, bringing the possibility to the customer to generate your own energy and inject the excess on the grid. Today, nine year after, almost 80% of all the distributed generation installed is made of small power plants until 75 kWp. However, the bidirectional meter installed in these units accounts only for the instantaneous difference between what is consumed and generated, leaving the customer unable to track his real energy consumption through the energy bill. To address this issue, this work proposes a monitoring and management system for units with distributed generation, capable of presenting real time consumption and generation measures, besides load control. It is proposed an independent measurement hardware based on the PZEM-004T module and on ESP32 microcontroller, who sends data through WiFi using the lightweight MQTT protocol. The data are received in a web application, designed using the Ruby on Rails framework, where are exhibited to the user and stored in a PostgreSQL database. The distributed generation in Brazil and in the world is presented, followed by a study about the smart meters and its role on the new grid paradigm. The developed system was installed in a study laboratory in Fortaleza, where it was availed in precision and performance to the user. The proposed system was capable of bringing up a potential energy saving and showing a need to improve the photovoltaic generation capability